2010
DOI: 10.1093/hmg/ddq449
|View full text |Cite
|
Sign up to set email alerts
|

Common CD36 SNPs reduce protein expression and may contribute to a protective atherogenic profile

Abstract: Membrane CD36 functions in the uptake of fatty acids (FAs), oxidized lipoproteins and in signal transduction after binding these ligands. In rodents, CD36 is implicated in abnormal lipid metabolism, inflammation and atherosclerosis. In humans, CD36 variants have been identified to influence free FA and high-density lipoprotein (HDL) levels and to associate with the risk of the metabolic syndrome, coronary artery disease and stroke. In this study, 15 common lipid-associated CD36 single nucleotide polymorphisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
120
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 126 publications
(133 citation statements)
references
References 74 publications
(86 reference statements)
11
120
0
2
Order By: Relevance
“…Although many of the studies including ours demonstrated the association of lack of Cd36 with metabolic syndrome features like insulin resistance or dyslipidemia (Aitman et al, 1997(Aitman et al, , 1999Febbraio et al, 1999;Pravenec et al, 2001;Seda et al, 2002), there are also reports suggesting that, in certain circumstances, the expression level of Cd36 actually correlates positively with unfavorable metabolic profile. Recently, it has been shown by Love-Gregory et al (2011) that in African-Americans the Cd36 variants that reduce protein expression appear to promote a protective metabolic profile, particularly concerning high-density lipoprotein and VLDL lipid levels Cd36 deficiency improves insulin sensitivity L Š edová et al (Love-Gregory et al, 2011). Also, the Cd36 knockout mice fed chow diet displayed lower fasting concentrations of glucose and insulin compared with wild-type controls (Hajri et al, 2002), similarly to PD.SHR4 congenics in the current study.…”
Section: Discussionsupporting
confidence: 58%
“…Although many of the studies including ours demonstrated the association of lack of Cd36 with metabolic syndrome features like insulin resistance or dyslipidemia (Aitman et al, 1997(Aitman et al, , 1999Febbraio et al, 1999;Pravenec et al, 2001;Seda et al, 2002), there are also reports suggesting that, in certain circumstances, the expression level of Cd36 actually correlates positively with unfavorable metabolic profile. Recently, it has been shown by Love-Gregory et al (2011) that in African-Americans the Cd36 variants that reduce protein expression appear to promote a protective metabolic profile, particularly concerning high-density lipoprotein and VLDL lipid levels Cd36 deficiency improves insulin sensitivity L Š edová et al (Love-Gregory et al, 2011). Also, the Cd36 knockout mice fed chow diet displayed lower fasting concentrations of glucose and insulin compared with wild-type controls (Hajri et al, 2002), similarly to PD.SHR4 congenics in the current study.…”
Section: Discussionsupporting
confidence: 58%
“…The rs1761665 SNP, in particular, is in strong LD with promoter SNPs previously shown to influence monocyte and platelet CD36 (58,59). Several of the promoter SNPs we identified here lie in close proximity to validated binding sites for PPAR and to methylation sites that associate with CD36 mRNA levels (Fig.…”
Section: 11mentioning
confidence: 52%
“…Association with left ventricular mass (8), a predictor of cardiovascular events (9), has also been reported. Common single nucleotide polymorphisms in the CD36 gene influence blood lipoprotein levels (10) and risk of the metabolic syndrome (11)(12)(13). The metabolic syndrome, a cluster of factors that include dyslipidemia, increases risk of heart disease and death from a heart attack (14).…”
mentioning
confidence: 99%